Kemampuan fiskal daerah dan pengaruh belanja daerah terhadap pertumbuhan ekonomi Kabupaten Tanjung Jabung Barat - Rahmad Suhendra; Muhammad Safri; Adi Bhakti (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
The purpose of this study was to determine and analyze 1) the proportion of regional expenditure in Tanjung Jabung Barat Regency; 2) regional fiscal capacity in West Tanjung Jabung Regency; 3) the ratio of regional financial independence of West Tanjung Jabung Regency; 4) the financial performance of the regional government of West Tanjung Jabung Regency and 5) the influence of regional spending on economic growth in the West Tanjung Jabung Regency. The data used in this study are secondary data. The analysis tool used is multiple linear regression. The results showed that the proportion of indirect expenditure to regional expenditure tended to decrease, while the proportion of direct expenditure to regional expenditure had an increase. The fiscal capacity of Tanjung Jabung Barat Regency for 11 years is still very lacking at the interval scale. The regional financial independence of West Tanjung Jabung Regency is in the low criteria. The regional financial performance of Tanjung Jabung Barat Regency is in the low and very low criteria. Regional expenditure influences economic growth in West Tanjung Jabung Regency. Keywords: Fiscal, Financial, Performance